Endoscope-Assisted Surgery vs. Burr-Hole Craniostomy for the Treatment of Chronic Subdural Hematoma: A Systemic Review and Meta-Analysis - Guo, Songyi; Gao, Wei; Cheng, Wen; Liang, Chuansheng; Wu, Anhua (Frontiers in Neurology, 2020)
Objectives: This article aims to evaluate the safety and effectiveness of endoscope-assisted surgery for chronic subdural hematoma (cSDH) in comparison with the burr-hole craniostomy. Methods: An electronic literature research was performed in MEDLINE, the Cochrane library, and EMBASE from the inception to February 18, 2020. A systematic review with meta-analyses was conducted to compare the efficacy of endoscope-assisted surgery with Burr-hole Craniostomy (BHC) surgery. Results: This meta-analysis included four studies comprising 441 patients. Endoscope-assisted surgery significantly decreased the risk of recurrence in patients with cSDH [odds ratio, 0.368; 95% confidence interval (CI), 0.178–0.759; P = 0.007; I2 = 0%]. The complication rate was also significantly lower in the endoscope-assisted group (OR, 0.249; 95% CI, 0.07–0.882; P = 0.031; I2 = 71.87%). Conclusion: We conducted the first meta-analysis of endoscope-assisted surgery for cSDH. The meta-analysis of four studies comprising 441 patients with cSDH suggests a significantly decreased risk of recurrence and postoperative complications after endoscope-assisted surgery. Therefore, endoscope-assisted surgery is effective and safe in treating cSDH.